Evaluasi Risiko Keselamatan dan Kesehatan Kerja pada Industri Furnitur Berbasis Metode HIRADC - Fandeli, Hary; Tomas, Micko (Jurnal Andalas: Rekayasa dan Penerapan Teknologi, 2025)
The furniture industry is one of the key contributors to Indonesia’s manufacturing sector, supporting national economic growth through exports and employment opportunities. However, this sector is also characterized by a high level of occupational hazards, including exposure to wood dust, machine noise, chemical solvents, and poor ergonomic practices. Small and medium-sized enterprises (SMEs) in particular often lack formal Occupational Health and Safety (OHS) management systems, making workers more vulnerable to accidents and occupational diseases. To address these challenges, this study aims to identify potential hazards, assess risk levels, and provide control recommendations in the furniture production process. The research employed the HIRADC method (Hazard Identification, Risk Assessment, and Determining Control) through field observation and interviews in one of the small and medium industries in Padang City, West Sumatra. The results indicate that most risks fall into the low to moderate categories, with one high-risk activity identified during wood sanding due to dust exposure. Recommended controls focus on applying the OHS control hierarchy, including engineering controls (local ventilation, noise reduction, ergonomic design), administrative measures (training and housekeeping), and the use of personal protective equipment. The findings conclude that HIRADC is effective in minimizing potential hazards and supporting the creation of a safe and sustainable working environment in the furniture industry.